KARAKTERISTIK LEMAK HASIL EKSTRAKSI BUAH TENGKAWANG ASAL KALIMANTAN BARAT MENGGUNAKAN DUA MACAM PELARUT - Raden Esa Pangersa Gusti; Zulnely (BRIN Publishing, 2015)
Indonesian Illipe nuts or known as ‘Tengkawang’ is one of essential export commodities from the non-wood forest products group. Unfortunately such traded commodityis still in originalshapeor unprocessed fruits in dry condition, thereby imparting only small-added values. One way to enhance their traded values is by processing the fruits into so-called illipe nut's fat. Currently, the illipe nut’s process is through the extraction of the respective fruits (nuts) using organic solvents. Different kinds of organic solvent could presumably affect the qualities of the resulting-fat. This paper studies the illipe nut’s extraction using two solvents: benzene and hexane. The resulting fat was then examined for it's qualities, i.e. yield, physico-chemical properties and chemical component content analysis using GC-MS (gas chromatography-mass spectrometry) pyrolysis. Results revealed that the hexane produces greator yield of storage time. The illipe nut's fat lower acid value, free fatic acid (FFA) content and lower iod number than those of benzene. Low acid value, FFA, and the iod number creates the fat which is more resistant against hydrolytic and oxidative rancidity, and longer storage time. GC-MS analysis indicated that the chemical components in the benzene-extracted illipe nut's fat was dominated by methyl-octadec-9- oneate, while those in hexane-extracted fat by methyl oleate (compound with saturated C-C bonds).Judging from the overall results, it seems the use of hexane is more prospective as solvent toextract the fat fromillipe nuts than benzene.